Iridium oxide supported on graphitized carbon for use as reversal tolerant anodes in pem fuel cells - Labi,Tita N (Department of Chemical Engineering, 2022)
One way in which potential reversal occurs in Proton Exchange Membrane Fuel Cells (PEMFCs) is when the H2 supply is insufficient to meet the load requirements of the cell. During cell voltage reversal, carbon oxidation and water electrolysis occur at the anode to maintain the supply of protons and electrons to the cathode. These reactions are nonspontaneous and consume energy from the membrane electrode assembly (MEA), causing irreversible damage through carbon corrosion. A material-based approach to prevent or reduce damage to the anode during cell reversal is to include an oxygen evolution reaction (OER) catalyst which will decrease the overpotential for water electrolysis. The addition of the OER catalyst to generate a reversal tolerant anode (RTA) will therefore decrease the occurrence of the carbon corrosion at cell potentials below -1.2 V. Due to the harsh conditions of fuel cell operation, the OER catalyst needs to provide both high activity and durability. Studies have shown that among the noble metal electrocatalysts, iridium (Ir) in its oxide form is among the highest for OER activity in acidic media. McCrory et al., (2013) also found that of all their tested metal oxide systems, IrOx was the most stable in acidic solutions. IrOx is an efficient catalyst for the OER but the use of pure IrOx is limited due to high costs and low surface area in its crystalline form. Several studies have therefore focused on supporting the IrOx on various materials to increase surface area and stability. Ideal catalyst supports used in electrochemical cells need to have a porous nanostructure and high electronic conductivity for electron transfer through the external circuit. Carbon remains the preferred commercial support due to its low costs, however, it undergoes corrosion under certain conditions during operation. Graphitized carbon supports have been gaining more attention due to their corrosion resistance and superior electrical conductivity. The aim of this study is therefore to use graphitized carbon supported iridium oxide to generate reversal tolerant anodes in an MEA. The IrOx supported graphitized carbon catalyst was synthesized using a microwave assisted polyol deposition technique. The supported catalyst was characterized using XRD, TEM, TGA, XPS and EDX analysis. The nanoparticles were well dispersed over the graphitised support and in the range of 4-10 nm. XPS analysis showed that the main oxidation states of Iridium were Ir3+ and Ir4+ which are proven to be the main states responsible for the OER. After comparison with commercial catalysts, it was found to have a good balance between activity and durability having an activity of 0.141 A/mg Ir towards the OER. The supported IrOx was included in the anode of an MEA at two different loadings (0.1 mg Ir /cm2 (1:1 Pt/Ir) and 0.06 mg Ir/cm2 (1:0.06 Pt/Ir)). The results showed that the addition of the OER did not compromise the performance of the MEA under normal operating conditions. Furthermore, the MEAs generated proved reversal tolerant capabilities by withstanding multiple, prolonged periods of fuel starvation by maintaining the cell potential in the water electrolysis potential range. The effects of fuel starvation were found to increase the ohmic resistance of the cell, possibly due to membrane dehydration and ionomer degradation. After testing, the MEAs were also characterised using XPS, SEM, cyclic voltammetry to determine the physical changes that occur during these events.